Optimizing Early Childhood Growth and Development through Health Screening, Dental Examination, and Interest-Talent Counseling: KKN-T UMSIDA Community Service Work Program in Pangkemiri Village : Optimalisasi Tumbuh Kembang Anak Usia Dini melalui Skrining Kesehatan, Pemeriksaan Gigi, dan Penyuluhan Minat-Bakat: Program Kerja Pengabdian Masyarakat KKN-T UMSIDA di Desa Pangkemiri - Aditama, Prima; Anjani, Adelia Rahma; Pratama, Alnesta Aurandhi Setya; Devi, Anintya Kurnia; Ardelia, Bella Putri; Baskoro, Deny Indra; Anandita , Eka; Adelia, Erine Hilda; Putri , Fara Nadhirah; Sandria, Feri; Pramono, Marsha Panca Suwita; Ghofur, Achmad Abdul; Dwikisaputra, Revaldo Ananda; Tillah, Rikhlah Qonita; Mubarokah, Umi Chabibah Siti; Anra, Yuana Veby (Universitas Muhammadiyah Sidoarjo, 2025)
The 2025 KKN-T Program Group 4 Pangkemiri Village carries the theme